Multiple Solutions for the Eigenvalue Problem of Nonlinear Fractional Differential Equations (Communications in Mathematical Research, 2021)
In this article, multiple solutions for the eigenvalue problem of nonlinearfractional differential equation is considered. We obtain the existence and multiplicityresults of positive solutions by using some fixed point theorems.